25 media personnel receive UMP aid - UMP, . (The New Straits Times Press (M) Bhd, 2015)
KUANTAN: Twenty-five members of the media in Pahang who were affected by the floods yet still carried on covering the situation received special aid from Universiti Maalaysia Pahang (UMP) yesterday